Synthesis of various arylated trifluoromethyl substituted indanes and indenes, and study of their biological activity. Issue 5 (1st February 2019) - Iakovenko, Roman O.; Chicca, Andrea; Nieri, Daniela; Reynoso-Moreno, Ines; Gertsch, Jürg; Krasavin, Mikhail; Vasilyev, Aleksander V.
Abstract: A series of 1-trifluoromethyl substituted indanes and indenes bearing aryl groups in positions 1 and/or 3 of the indane core have been synthesized mainly by electrophilic cyclization and arylation of the corresponding trifluoromethylated allyl and propargyl alcohols. The distinctly lipophilic compounds thus obtained were tested against various components of human endocannabinoid system. None of the compounds displayed affinity toward CB1 or CB2 receptors. Two compounds inhibited monoacylglycerol lipase (MAGL) and three compounds showed inhibition of anandamide (AEA) uptake. The latter can be related to the low-micromolar inhibition of fatty acid amide hydrolase (FAAH) inhibition displayed by one of these compounds. Graphical abstract: